An Interpretation Of Cash Waqf For Islamic Economic Growth And Development From The Perspective Of Waqf Nazhir - Dliyaul Muflihin, Mohammad; Faizah, Nur; Suryani Lating, Ade Irma; Anggraini Aripratiwi, Ratna; Fabian Susanto, Febry (Program Studi Manajemen Zakat dan Wakaf, 2025)
In 2021, the Indonesian Waqf Board (Badan Wakaf Indonesia) reported the potential of cash waqf to reach approximately IDR 180 trillion annually. As of March 2023, the actual collected amount of cash waqf stood at IDR 2.07 trillion, which includes the accumulated issuance of Cash Waqf Linked Sukuk (CWLS) totaling IDR 678.15 billion. Nevertheless, the effectiveness of cash waqf as an instrument for economic development is highly contingent upon the management capabilities of waqf administrators (nadzir). The extent to which nadzir are able to manage cash waqf productively significantly influences its potential social and economic impact. This study aims to explore the interpretation of cash waqf as an Islamic public financial instrument for fostering economic development from the perspective of waqf administrators. Employing a qualitative methodology with a Husserlian phenomenological approach, the study distinguishes between noema and noesis through the process of epoche. The findings suggest that cash waqf, as a public financial instrument, must be utilized productively to support long-term economic sustainability. At the macroeconomic level, waqf is positioned as a strategic tool for advancing national economic development. The study recommends concerted efforts among government entities, waqf institutions, and the wider public to strengthen institutional capacity, human resources, technological infrastructure, and public awareness, all of which are critical for enhancing the productive utilization of waqf.